1997
DOI: 10.1295/polymj.29.184
|View full text |Cite
|
Sign up to set email alerts
|

Second-Order Optical Nonlinearity of Novel Methacrylate Polymer with Pendant Disazo Dye Chromophore Containing a Perfluorobutylsulfonyl Group

Abstract: KEY WORDSNonlinear Optics (NLO) / Second-Order Nonlinear Optical Coefficient (d33) / Second Harmonic Generation (SHG) / Perfluorobutylsulfonyl / Disazo Dye / Relaxation Behavior / Potential applications like optical communications and electrooptics have motivated researchers to flourish the area of nonlinear optics (NLO). 1 -4 To get a large second-order nonlinear optical coefficient (d 33 ), dyes terminated with strong electron-withdrawing and donating groups at both the ends of the molecule separated by a n-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Thus, when our systems were compared with other systems with similar structures and T g values, such as poly(methyl methacrylate) (PMMA)‐ or PS‐based NLO polymers, in which hydrogen bonding does not occur, better stability was observed. A discussion of the stability of PMMA‐ and PS‐based NLO polymers can be found in the literature 47–49. Figure 9 further shows that the signal disappeared completely as the temperature rose above T g .…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, when our systems were compared with other systems with similar structures and T g values, such as poly(methyl methacrylate) (PMMA)‐ or PS‐based NLO polymers, in which hydrogen bonding does not occur, better stability was observed. A discussion of the stability of PMMA‐ and PS‐based NLO polymers can be found in the literature 47–49. Figure 9 further shows that the signal disappeared completely as the temperature rose above T g .…”
Section: Resultsmentioning
confidence: 84%
“…A discussion of the stability of PMMA-and PS-based NLO polymers can be found in the literature. [47][48][49] Figure 9 further shows that the signal disappeared completely as the temperature rose above T g . However, the same magnitude of the SHG signal was recovered from this sample after it was repoled by corona discharging, and this indicated that the NLO chromophore was not damaged after experiencing a high temperature.…”
Section: Nlo Properties Of the Polyurethanesmentioning
confidence: 83%